Association of Haemoglobin A1c Level with the Severity of Coronary Artery Disease in Non-diabetic Patients with Non-STSegment Elevation Myocardial Infarction - Md Mamunuzzaman, -; Ali, Mahboob; Uddin, Mir Jamal; Nabi, Shaila; Karmoker, Kajal Kumar; Razzaque, Muhammed Aminur; Das, Pinaki Ranjan; Masum, Md Sazzad; Rashid, Mohammad Bazlur; Romel, Syed Mohammad Ali (Bangladesh Heart Journal, 2021)
Background: In nondiabetic patients with non-STsegment– elevation myocardial infarction, hyperglycemia may be associated with adverse outcome. Objective: To find out the association between HbA1c levels and the severity of coronary artery disease in non-diabetic patients with non-ST-segment elevation myocardial infarction Methods: This cross sectional analytical study was carried out at the National Institute of Cardiovascular Diseases (NICVD), Dhaka, during the period from July, 2012 to May, 2013. This study was done with an aim to find out the association between the HbA1c level and the angiographic severity of coronary artery disease in patients with non-ST- elevation myocardial infarction without diabetes mellitus. A total of 170 patients with NSTEMI without diabetes mellitus who agreed to undergo coronary angiography were included in the study. Eighty five patients were selected having HbA1c <5.7% (Group I) and 85 patients were selected having HbA1c ranging from 5.7% to 6.4% (Group II). Severity of the Coronary Artery Disease (CAD) was assessed by angiographic vessel score, and Gensini score. Results: The mean age of the studied patients was 51.0±9.0 years ranging from 30 to 80 years and male to female ratio was 4.5:1. The incidence of hypertension and level of RBS were significantly higher in group II than group I. The HbA1c level increased in accordance with the vessel score increment. There was a significant difference of the mean value of HbA1c among the vessel involvement groups. In this study mild CAD (scored”36) was significantly higher in group I and moderate to severe CAD (score>36) was significantly higher in group II according to Gensini score. This study showed a positive correlation between HbA1c and vessel score (r=0.47, p=0.01) and also between HbA1c and Gensini score (r=0.41, p=0.01). Conclusion: Elevated HbA1c levels in non-diabetic non- ST- elevation myocardial infarction patients are associated with the severity of coronary artery disease. Bangladesh Heart Journal 2020; 35(2) : 134-139